2019
DOI: 10.1002/ece3.4871
|View full text |Cite
|
Sign up to set email alerts
|

Habitat differentiation among three Nigeria–Cameroon chimpanzee (Pan troglodytes ellioti) populations

Abstract: Ecological niche models (ENMs) are often used to predict species distribution patterns from datasets that describe abiotic and biotic factors at coarse spatial scales. Ground‐truthing ENMs provide important information about how these factors relate to species‐specific requirements at a scale that is biologically relevant for the species. Chimpanzees are territorial and have a predominantly frugivorous diet. The spatial and temporal variation in fruit availability for different chimpanzee populations is thus c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 88 publications
(127 reference statements)
1
19
0
Order By: Relevance
“…The presence of the forest-savannah mosaic in MDNP increases the heterogeneity of both habitat characteristics and climatic conditions even more (Abwe et al 2019) and, consequently, might also increase the geographical heterogeneity of the mean nest decay rate. At Ugalla, Tanzania, Stewart et al (2011) and Hernandez-Aguilar et al (2013) showed how environmental characteristics determined the nesting site choice, highlighting the effects of habitat heterogeneity on the nest decay rate variation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The presence of the forest-savannah mosaic in MDNP increases the heterogeneity of both habitat characteristics and climatic conditions even more (Abwe et al 2019) and, consequently, might also increase the geographical heterogeneity of the mean nest decay rate. At Ugalla, Tanzania, Stewart et al (2011) and Hernandez-Aguilar et al (2013) showed how environmental characteristics determined the nesting site choice, highlighting the effects of habitat heterogeneity on the nest decay rate variation.…”
Section: Discussionmentioning
confidence: 99%
“…About half of the park in the southern sector is covered by lowland tropical forest and the other half, in the northern sector, is covered by Sudano-Guinean tree and woodland savannah with a wide forest-savannah mosaic in between, which promotes a very high level of biodiversity (White 1983;WCS 2017). The climate in this region has two seasons: a rainy season from mid-April to mid-October, and a dry season from mid-October to mid-April (MINFOF 2007;Abwe et al 2019). The relief is nearly flat, with a north-to-south altitudinal decline from 930 to 650 m asl (Bobo and Weladji 2011).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses offer exploratory insights into intermediary landscape-level factors between regional level analyses and site-based investigations of chimpanzee habitat characteristics. Regional level analyses often fail to account for smaller-scale processes and variation that may also impact habitat suitability (Abwe et al 2019), and therefore overlook smaller-scale environmental processes like those we describe here. Our results offer a method of ground-truthing the conclusions of larger-scaled studies and broad-scaled ENMs with regard to the governing environmental variables to chimpanzee distribution.…”
Section: Discussionmentioning
confidence: 95%
“…A number of large-scale chimpanzee ecological niche models (ENMs), or distribution models, have offered insights into the factors that influence chimpanzee distribution and site occupancy, such as distance to roads or rivers, forest coverage, climatic and human influences (Junker et al 2012;Sesink Clee et al 2015;Foerster et al 2016;Jantz et al 2016;Abwe et al 2019;Heinicke et al 2019a; Barratt et al 2020), although these models typically evaluate characteristics of the chimpanzee niche at large. Larger-scale analyses depend on data obtained from remote sensing (e.g., percent forest cover, climate averages, human population indices, land cover classifications, distance to roads and rivers) as proxies for smaller-scale metrics like habitat heterogeneity or food species assemblages.…”
Section: Introductionmentioning
confidence: 99%